Microporous fat unit-containing polyimide film material and preparation method thereof

By designing a fat-containing polyamide ester structure in the polyimide film material to form a microporous structure, the safety problems and the problem of excessive dielectric constant of the polyimide film when used at high temperatures are solved, and the comprehensive optimization of the material's high mechanical properties, good heat resistance and low dielectric constant is achieved.

CN119842074AActive Publication Date: 2025-04-18CHANGCHUN INSTITUTE OF APPLIED CHEMISTRY CHINESE ACADEMY OF SCIENCES
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510067836.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-04-18
Estimated Expiration
2045-01-16

AI Technical Summary

Technical Problem

Existing polyimide film materials are prone to shrinkage and melting when used at high temperatures, resulting in safety accidents in lithium-ion batteries. At the same time, their high dielectric constant is not suitable for the integrated development of microelectronic products.

Method used

By designing the structure of the fat-containing polyamide esters, a multi-porous structure is introduced in the imidation reaction, and uniform pores are formed by using the cyclization of the molecular chain and the branched chain shedding process to reduce the dielectric constant and improve mechanical properties.

Benefits of technology

The preparation of polyimide film materials with multi-porous fat-containing units has been realized, with high mechanical properties, good heat resistance and low dielectric constant, and is suitable for insulating materials for lithium-ion battery separators and microelectronic products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the field of polyimide materials, in particular to a microporous fat unit-containing polyimide film material and a preparation method thereof. Aiming at the problems that microporous fat unit-containing polyimide has good solubility, phase separation is difficult to occur in an imidization process, and pore forming is not facilitated, a specific compound containing an ether bond or an ester group and monohydroxyl-terminated poly (dimethyl siloxane) are specifically grafted onto a polymer molecular chain; and phase separation is gradually and uniformly generated in the film along with chemical change on a molecular chain, and natural pores are gradually formed, so that the intrinsic characteristics of polyimide are kept to the maximum extent while the pore diameter uniformity is ensured. In addition, a conventional polyimide film production process and production equipment which are highest in technical maturity and production efficiency at present are adopted, so that large-scale production of the porous polyimide film is facilitated, and intrinsic performance of a polyimide material is reserved; and the problems of film degradation and non-uniform pores and pore diameters caused by the increase of subsequent treatment procedures are avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polyimide materials, in particular to a multi-microporous polyimide film material containing fat units and a preparation method thereof. Background Art

[0002] Polyimide (PI) is a special engineering plastic containing an imide ring on the molecular chain. It has many excellent properties such as dielectric properties, heat resistance, mechanical properties, chemical stability and self-extinguishing properties. The most noteworthy of the above properties is that it far exceeds the heat resistance of other polymer materials. Most of the research work at home and abroad is centered on the high heat resistance of PI. In the field of new energy, the safety of lithium-ion batteries has attracted more and more attention from the whole society. The reason for the safety accidents of lithium batteries is that the battery separators with the largest consumption at present are polyethylene and polypropylene materials. The temperature resistance of these materials is low, and the maximum operating temperature is only 170℃. The battery will generate heat during the charging and discharging process. When the internal heat accumulates excessively and the temperature reaches the upper limit of the separator, the separator will shrink and melt, causing the positive and negative electrodes of the battery to contact and short-circuit, causing the battery to burn and explode. In addition, the weak polarity of polyolefin materials has poor wettability to the electrolyte, and the liquid absorption of the separator and the passage of lithium ions are inhibited, which will affect the efficiency of the battery. PI has heat resistance far exceeding that of other polymer materials. Ordinary PI can be used for a long time under conditions above 300°C. At the same time, the carbonyl group on the imide ring has a strong polarity and has good wetting properties for the electrolyte. The preparation of a PI separator suitable for lithium-ion secondary batteries will be the best solution to improve the safety and service life of lithium batteries.

[0003] The presence of imide rings is the fundamental reason why PI is different from other polymer materials in terms of heat resistance. Among PIs with different structures, PIs with aromatic structures as the main component have better heat resistance, but PIs with fully aromatic structures have higher dielectric constants while improving heat resistance. The application areas of porous polyimide films are far more than the new energy field. In the context of the increasing integration of microelectronic products, materials with high dielectric constants will lose some of their competitive advantages. Specifically, as information technology advances at an increasingly rapid pace, microelectronic products are gradually developing towards miniaturization and ultra-thinness, the integration of electrical components is getting higher and higher, the wiring spacing on the chip is getting smaller, and capacitive coupling and cross-interference will occur between adjacent wirings, causing signal hysteresis. This more integrated electronic component requires the insulating layer to have a lower dielectric constant and dielectric loss. At present, any dense PI film prepared by any commercial chemical structure cannot meet the requirements.

[0004] If you want to get a PI film with higher dielectric properties, on the one hand, you can create some micropores inside the film based on the physical structure of the film, and form a PI-air two-phase system, which can greatly reduce the dielectric constant and dielectric loss of the material. In the method of producing polyimide film by thermal method known in the industry, during the thermal imidization process, as the solvent gradually evaporates at high temperature, the molecular chain undergoes a cyclization reaction after reaching a specific temperature, and the branch chain begins to fall off at this time. The detached branch chain remains in the system to promote the occurrence of phase separation. In the traditional polyimide film production process, some polyimides with certain structures will also undergo microphase separation during the imidization process. This is because the solvent volatilization and the degree of molecular chain cyclization increase in the production of traditional polyimide films, which leads to a decrease in polymer solubility. In the production of traditional polyimide films, the water removed by imidization and the temperature of solvent volatilization are far lower than the glass transition temperature of the polymer, which leads to the rapid filling of the pores left after the water and solvent evaporate by the softened polymer. Therefore, the traditional polyimide film is dense and non-porous.

[0005] At present, the preparation of porous polyimide films can be roughly divided into the following types: doping method (inorganic particles or hollow microspheres), template method, electrospinning method, and phase conversion method. From the pore state of the film, it can be divided into open pores, closed pores, and through pores. The inorganic particle doping method and template method are mostly used to prepare open pores. The inorganic particle doping method is to mix inorganic particles into the polyamide acid glue solution, and use strong acid to remove the particles after film formation. Since the acid solution cannot completely penetrate into the film, some particles will remain and a large number of through holes cannot be obtained. At the same time, acid dissolution and etching will also have a certain deterioration effect on the film, affecting the film performance. In addition, due to the inorganic particle solidification effect caused by static electricity, it is difficult to evenly mix into the high viscosity glue solution, resulting in uneven film pore size and distribution. The pore formation method of the template method is roughly the same as that of the inorganic particle doping method, and strong acid treatment is also required in the end. The disadvantages are also roughly the same. At the same time, this method is not suitable for large-scale production. The pores of the film prepared by electrospinning pass through both sides of the film, the pore size is too large, the uniformity is poor, and the mechanical properties are very poor. It is difficult to meet the requirements of large-capacity and high-power lithium-ion batteries. At the same time, this method also has the problem of being difficult to mass-produce on a large scale. The phase conversion method is to prepare polyamide acid into a semi-dry film and immerse it in a poor solvent, and promote the phase separation of the system from the outside to the inside. After the phase separation, the channel where the solvent is leached forms pores. Since the phase separation occurs from the outside to the inside, and the degree of phase separation varies greatly, the pore size formed by this method varies greatly on the inside and outside of the film, and the distribution is uneven; in addition, this method uses external force to quickly promote phase separation, which is difficult to ensure the uniformity of pore size and pore distribution, and pore collapse is inevitable in the subsequent imidization process. The films prepared by the hollow microsphere doping method are mostly closed-cell structures. Since it is difficult to overcome the agglomeration effect of microparticles, the uniformity of mixing directly determines the uniformity of the pores. The above methods can form microporous structures on polyimide films, but each method has major defects, and the complicated process makes it difficult to achieve large-scale production of films.

[0006] On the other hand, based on the fact that dielectric properties are intrinsic properties of materials, PI containing fat units can have a lower dielectric constant from a structural perspective. The PI containing fat units mentioned here refers to polyimides with aliphatic chains, aliphatic rings, and spirocyclic structures containing two or more carbon atoms between two aromatic rings. With a fat unit structure as the main molecular chain, polyimides containing fat units are characterized by weak molecular chain rigidity, better flexibility and ductility of the polymer, and better ability to prevent lithium crystals in the electrolyte from piercing as lithium-ion battery separators. At the same time, the heat resistance of the imide ring on the molecular chain is much higher than that of other types of polymer materials. However, polyimides containing fat units have excellent solubility, which is not conducive to phase separation and void formation during the cyclization process. Therefore, how to promote phase separation of polyimides containing fat units during the imidization process is a difficult point. Summary of the invention

[0007] In view of this, the technical problem to be solved by the present invention is to provide a microporous fat-unit-containing polyimide film material and a preparation method thereof. The preparation method provided by the present invention can obtain a microporous fat-unit-containing polyimide film material with uniform pore size and porosity, which has high mechanical properties and heat resistance, high porosity and good dielectric properties.

[0008] The present invention provides a multi-microporous fat-unit-containing polyimide film material, which is obtained by imidization reaction of a material including a fat-unit-containing polyamide ester having a structure of formula I;

[0009]

[0010] Wherein, said z≥1000;

[0011] The Ar 1 and Ar 2 are independently selected from substituted or unsubstituted aromatic groups, substituted or unsubstituted heteroaromatic groups, substituted or unsubstituted aliphatic groups, and the Ar 1 and Ar 2 are not simultaneously selected from substituted or unsubstituted aromatic groups or substituted or unsubstituted heteroaromatic groups;

[0012] The M 1 and M 2 Independently selected from substituted or unsubstituted C 1 ~C 60 Ether-bonded aliphatic groups, substituted or unsubstituted C 1 ~C 60 Thioether-containing aliphatic groups, substituted or unsubstituted C 1 ~C 60 An ester-containing aliphatic group or a poly(dimethylsiloxane) group, and the M 1 and M 2 Same or different.

[0013] The structural unit of the polyamide ester containing fat units of the present invention has M 1 and M 2 Side chain groups, preferably, the M 1 and M 2 Independently selected from substituted or unsubstituted C 3 ~C 30 Ether-bonded aliphatic groups, substituted or unsubstituted C 3 ~C 30 Thioether-containing aliphatic groups, substituted or unsubstituted C 3 ~C 30 One of an ester-containing aliphatic group or a poly(dimethylsiloxane) group having a structure of Formula Ia;

[0014]

[0015] The x is ≥ 1, preferably 5 to 10;

[0016] The R is a fatty chain.

[0017] The aliphatic structure of the aliphatic group may be a straight chain aliphatic structure or a branched aliphatic structure or a structure with an aliphatic ring; the aliphatic group may also be substituted with a functional group, which includes but is not limited to the following structures: -Cl, -F or -CF 3 The above-mentioned ether bond-containing aliphatic group, thioether bond-containing aliphatic group and ester group-containing aliphatic group can be a fatty structure containing one or more ether bonds, thioether bonds and ester groups.

[0018] In certain embodiments of the present invention, the substituted or unsubstituted C 1 ~C 60 The ether bond-containing aliphatic group has the structure of formula Ib to formula Ih:

[0019]

[0020] Among them, 1 、j 2 and j 3 are independently at least 1, and j 1 、j 2 and j 3 The sum is at most 59; 4 and j 5 are independently at least 1, and j 4 and j 5 The sum is at most 59; 6 and j 7 are independently at least 1, and j 6 and j 7 The sum is at most 59.

[0021] In certain embodiments of the present invention, the substituted or unsubstituted C 3 ~C 30 The ester-containing aliphatic group has a structure of formula Ii to formula Il:

[0022]

[0023] The polyamide ester containing fat units having a structure of formula I of the present invention has a poly(dimethylsiloxane) group, and the molar amount of the poly(dimethylsiloxane) group accounts for 10% of the molar amount of the poly(dimethylsiloxane) group. 1 and M 2The total molar amount is 2% to 50%, preferably 17% to 22%. If it is less than 2%, the film will not form pores, and if it is greater than 50%, the pore size will be too large and the mechanical properties of the film will be greatly reduced. 1 and M 2 The side chain structure, under the action of heat, the molecular chain undergoes cyclization and branching falls off, the boiling point of the compound after falling off is much higher than the temperature of the falling off point, and it remains in the film without immediate volatilization, promoting the occurrence of phase separation of the system, and the self-supporting property of the film becomes larger and larger as the temperature rises. When the temperature reaches the temperature point where the falling compound volatilizes in large quantities, the self-supporting property inside the film is good enough at this time, and the original space occupied by the falling branch after volatilization is retained, and finally intrinsic micropores are formed in the polyimide film. The pore-forming compound of the present invention is evenly distributed on the polymer main chain in the form of chemical bonds, and the pore size and pore uniformity formed are more excellent.

[0024] The structural unit of the polyamide ester containing fat units of the present invention is Ar 1 and Ar 2 Preferably, Ar 1 With the formula Ar 1 -a to Ar 1 - one or more of the k structures;

[0025]

[0026]

[0027] The Ar 2 With the formula Ar 2 -a to Ar 2 -e structure of one or more;

[0028]

[0029] Wherein, X is selected from hydrogen, alkyl, cycloalkyl, aryl, fluoroalkyl, hydroxyl, alkoxy, phenoxy, cyano, nitro, amino, acetylamino, ester, acyl, halide or carboxyl; preferably, X is selected from -H, -Br, -Cl, -F, -NO 2 、-CN、-H、-CH 3 、-CH 2 CH 3 、-CH 2 CH 2 CH 3 , isopropyl, isobutyl, tert-butyl, cyclopentyl, cyclohexyl, phenyl or naphthyl.

[0030] The y is independently an integer of 1 to 4;

[0031] The R 1 and R 2 One independently selected from the groups represented by the structures of Formula 1 to Formula 13;

[0032]

[0033] Among them, the X 1 and X 2 is independently selected from hydrogen, alkyl, cycloalkyl, aryl, fluoroalkyl, hydroxyl, alkoxy, phenoxy, cyano, nitro, amino, acetylamino, ester, acyl, halide or carboxyl; preferably, the X 1 and X 2 Independently selected from -H, -Br, -Cl, -F, -NO 2 、-CN、-H、-CH 3 、-CH 2 CH 3 、-CH 2 CH 2 CH 3 , isopropyl, isobutyl, tert-butyl, cyclopentyl, cyclohexyl, phenyl or naphthyl.

[0034] The R 3 Selected from C 1 Alkyl or C 1 The above fluorinated alkyl groups.

[0035] Preferably, the R 3 Selected from the group consisting of 3 -a~Formula R 3 -f One of the structural groups:

[0036]

[0037] Where g≥1.

[0038] The above formula Ar 1 -a to Ar 1 -k, formula Ar 1 -f The structure shown is preferably Formula Ar 1 The structure shown in -g is preferably Formula Ar 1 The structure shown in -h is preferably Formula Ar 1 The structure shown in -i is preferably Formula Ar 1 The structure shown in -j is preferably Formula Ar 1 The structure shown in -1 is preferably Formula Ar 1 The structure shown in -m is preferably Formula Ar 1 The structure shown in -o is preferably Formula Ar 1 The structure shown in -p is preferably Formula Ar 1 The structure shown by -s is preferably

[0039] The microporous fat-unit-containing polyimide film material provided by the present invention has a structure shown in Formula II;

[0040]

[0041] Wherein, the Ar 1 ,Ar 2 and z are the same as in the above formula I and are not repeated herein.

[0042] The present invention also provides a method for preparing the microporous polyimide film material containing fat units as described in any of the above technical solutions, comprising the following steps: subjecting a material containing polyamide ester containing fat units to an imidization reaction to obtain the microporous polyimide film material containing fat units. The polyamide ester containing fat units described in the present invention is the same as the above, and will not be described in detail.

[0043] The reaction formula for obtaining a microporous polyimide film material containing fat units by imidization reaction of the polyamide ester containing fat units of the present invention is as follows:

[0044]

[0045] The temperature of the imidization reaction of the present invention is 50°C to 350°C, preferably 80°C to 300°C, and the time of the imidization reaction is 0.3h to 30h. The present invention designs the structure of polyamide ester containing fat units, that is, only changes the structure of the intermediate, but does not change the final structure of the polyimide material containing fat units. Through the above-mentioned heat treatment in the temperature range, the polyamide ester containing fat units can be gradually imidized and transformed into a microporous film structure of polyimide containing fat units; the design idea of ​​polyamide ester containing fat units as an intermediate evenly distributes the pore-forming compound on the polymer molecular chain in the form of chemical bonds, and becomes a whole with the polymer before falling off, and forms intrinsic pores in situ after falling off, which is essentially different from other existing methods of forming pores on polyimide films. Since the pores are formed in situ after the side chains of the polyamide ester containing fat units fall off, the pore size and distribution of the obtained polyimide film containing fat units are uniform. In addition, the method of the present invention can completely adopt the conventional thermal imidization method for continuous film formation, avoiding the adverse effects of adding other processes on the film performance. At the same time, the present invention adopts the most mature and efficient thermal imidization polyimide film preparation method in the prior art, which is more conducive to the large-scale production of microporous polyimide films while maximizing the intrinsic properties of polyimide, and the batch stability is more excellent.

[0046] The present invention adopts a step-by-step heating method according to the progress of imidization of the polyamide ester containing fat units to control the formation of voids. Specifically, the present invention sequentially subjects the glue solution including the polyamide ester containing fat units to a pre-baking and curing stage treatment and a post-baking high-temperature treatment to obtain a microporous polyimide film material containing fat units; wherein the pre-baking and curing stage treatment is also called a solvent volatilization stage treatment, the temperature of the pre-baking and curing stage treatment is 50°C to 150°C, preferably 80°C to 120°C, and the time of the pre-baking and curing stage treatment is 0.1h to 10.0h. The present invention first subjects the material including the polyamide ester containing fat units to the pre-baking and curing stage treatment to volatilize the solvent of the material to obtain a film material, and the obtained film material is a semi-dry film and still contains residual solvent.

[0047] The present invention performs the pre-baking and curing stage treatment on the material including the polyamide ester containing fat units, and then performs the post-baking high-temperature treatment on the obtained film material; the post-baking high-temperature treatment includes the imidization stage treatment and the pore-forming material escape stage treatment performed in sequence, the temperature of the imidization stage treatment is 100℃~250℃, preferably 120℃~180℃, and the time of the imidization stage treatment is 0.1h~10.0h; the temperature of the pore-forming material escape stage treatment is 150℃~350℃, preferably 150℃~300℃, more preferably 180℃~270℃, and the time of the pore-forming material escape stage treatment is 0.1h~10.0h. The chemical and physical changes in the above three stages are not necessarily carried out completely according to the naming of each stage, and the physical and chemical changes in each stage will overlap. For the sake of clarity, the main physical and chemical changes of the stage are named. In addition to the above-mentioned segmented heating method, the imidization can also be carried out by gradient heating, and the preferred heating rate is 0.1℃ / min~5℃ / min. The above film preparation process can also be adjusted according to the actual continuous film production.

[0048] In some embodiments of the present invention, the present invention coats the adhesive liquid containing fat unit polyamide ester on a carrier, and sequentially performs a pre-baking curing stage treatment and a post-baking high temperature treatment to obtain a multi-microporous fat unit polyimide film material. The present invention coats the adhesive liquid containing fat unit polyamide ester on a carrier using adhesive liquid coating equipment well known in the art, and the coating method can be slit-type scraping, baffle-type scraping, spin coating, spray coating, and cast coating; the carrier can be a continuous steel strip, polyester film, copper foil, aluminum foil, glass, or mirror steel plate. The present invention performs an imidization reaction on the material containing fat unit polyamide ester, and in order to facilitate pore formation, a surfactant, a nucleating agent, etc. can be added to perform an imidization reaction together with the material.

[0049] In other embodiments of the present invention, a glue liquid including polyamide ester containing fat units is coated on a carrier, and after a pre-baking and curing stage is performed and the glue film is cured into a semi-dry film, the semi-dry film is peeled off the carrier and supported by a hollow frame. For example, the edge of the film is fixed by using needle plates, chain clamps and other equipment used in the existing polyimide film production, and the film is supported and placed in a high temperature environment to realize the imidization process. This process realizes the escape of volatiles to both sides of the film, avoiding the situation where the solvent evaporates on one side and causes uneven pores on both sides.

[0050] The above-mentioned film preparation process matches the conventional polyimide film production process. There is no need to add new processes and new equipment on the basis of the conventional polyimide film production process and equipment. The film preparation process is efficient and low-cost, which is conducive to the rapid realization of large-scale industrial production of microporous fat-containing polyimide films.

[0051] Preferably, the method for preparing the microporous polyimide film material containing fat units provided by the present invention comprises the following steps:

[0052] S1) reacting a monohydroxy compound with a dianhydride having a structure of formula a; the monohydroxy compound is selected from substituted or unsubstituted C 1 ~C 60 Ether-bonded aliphatic alcohols, substituted or unsubstituted C 1 ~C 60 Thioether-containing aliphatic alcohols, substituted or unsubstituted C 1 ~C 60 One or more of the ester-containing fatty alcohols and a monohydroxy-terminated poly(dimethylsiloxane) having a structure of formula b;

[0053]

[0054] S2) polymerizing the diamine having the structure of formula c and the reaction product obtained in step S1);

[0055] H 2 N-Ar 2 -NH 2 Formula c;

[0056] S3) performing an imidization reaction on the product obtained in step S2) to obtain a microporous polyimide film material containing fat units.

[0057] The reaction formula of the preparation method of the above-mentioned multi-microporous fat-containing polyimide film material is as follows:

[0058]

[0059] Specifically, in step S1) of the present invention, a monohydroxy compound and a dianhydride having a structure of formula a are reacted under the action of a catalyst, or a monohydroxy compound and a dianhydride having a structure of formula a are directly reacted without using a catalyst; wherein the monohydroxy compound is selected from substituted or unsubstituted C 1 ~C 60 Ether-bonded aliphatic alcohols, substituted or unsubstituted C 1 ~C 60 Thioether-containing aliphatic alcohols, substituted or unsubstituted C 1 ~C 60 One or more of ester-containing fatty alcohols and monohydroxy-terminated poly(dimethylsiloxane). Preferably, the monohydroxy compound is selected from substituted or unsubstituted C 3 ~C 30 Aliphatic alcohols, substituted or unsubstituted C 3 ~C 30 Ether-bonded aliphatic alcohols, substituted or unsubstituted C 3 ~C30 Thioether-containing aliphatic alcohols, substituted or unsubstituted C 3 ~C 30 One or more of the ester-containing fatty alcohols and a monohydroxy-terminated poly(dimethylsiloxane) having a structure of formula b, wherein R and x in formula b are the same as R and x in the aforementioned formula Ia, and are not described in detail. In certain embodiments of the present invention, the substituted or unsubstituted C 1 ~C 60 Ether-bonded aliphatic alcohols include

[0060] Among them, 1 、j 2 and j 3 are independently at least 1, and j 1 、j 2 and j 3 The sum is at most 59; 4 and j 5 are independently at least 1, and j 4 and j 5 The sum is at most 59; 6 and j 7 are independently at least 1, and j 6 and j 7 The sum is at most 59; the above substituted or unsubstituted C 3 ~C 30 Ester-containing fatty alcohols include

[0061]

[0062] The reaction in step S1) of the present invention is an esterification reaction, and the reaction temperature is -5°C to 60°C, preferably 0°C to 10°C; the reaction time in step S1) of the present invention is 16h to 25h, and a part of the product obtained by the reaction is a completely esterified diacid diester, and its structure is Another part is a partial esterification product, and another part is a partial esterification product, whose structural formula is The M 1 and M 2 Same as above, no further elaboration.

[0063] In step S1) of the present invention, the monohydroxyl-terminated poly(dimethylsiloxane) accounts for 2% to 50% of the total amount of the monohydroxyl compound, preferably 12% to 18%. The present invention can effectively control the intrinsic micropore size and pore density of the film by adjusting the proportion of the monohydroxyl-terminated poly(dimethylsiloxane) in the monohydroxyl compound.

[0064] The catalyst in step S1) of the present invention may be added selectively or not, and the catalyst may be a tertiary amine well known in the art. The reaction in step S1) of the present invention is carried out in a solvent, and the solvent includes but is not limited to the following compounds: N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), N-methylpyrrolidone (NMP), γ-butyrolactone, toluene, xylene, dichlorobenzene, ethanol, isopropanol, n-butanol, cyclohexanol, ethylene glycol, ethylene glycol monoethyl ether, ethylene glycol dimethyl ether, 2,2′-dimethoxyethyl ether, acetone, acetonitrile, methyl ethyl ketone, cyclohexanone, tetrahydrofuran, dioxane, N-cyclohexylpyrrolidone, dimethyl sulfoxide, cresol, m-cresol, ethyl acetate, etc., or a mixture of two or more thereof.

[0065] The inventors selected the above-mentioned monohydroxy compounds as grafting compounds based on the analysis of chemical structure and physical properties and a large number of experiments. These monohydroxy compounds are evenly distributed on the main chain of the polymer. During the baking process, as the solvent continues to volatilize, the amidation reaction gradually occurs in the system at a specific temperature point, and significant phase separation occurs. At this time, the branched compounds that fall off during the amidation reaction have a higher boiling point, and most of the branched compounds that fall off remain in the main body of the film. As the temperature rises, the film gradually forms a certain self-supporting ability. At this time, the side chains that fall off begin to escape, and the space they occupy is left behind, thereby forming an aperture. In addition, since the present invention adopts conventional polyimide film production processes and equipment to realize the production of polyimide films containing fat units, the obtained polyimide films containing fat units have a very high degree of cyclization, and no other processes need to be added, so that the excellent properties of polyimide can be retained to the greatest extent.

[0066] In the step S1) of the present invention, after the monohydroxy compound and the dianhydride having the structure of formula a are reacted, the diamine having the structure of formula c and the reaction product obtained in the step S1) are polymerized.

[0067] Specifically, step S2) of the present invention includes but is not limited to the following implementation methods:

[0068] Method 1: The reaction product obtained in step S1) is subjected to an acyl chloride reaction, and then the obtained material is subjected to a polymerization reaction with a diamine having a structure of formula c to obtain a viscous polyamide ester glue containing fat units. The acyl chloride reagent of the acyl chloride reaction of the present invention is SOCl 2 In this process, the reaction product obtained in step S1) is mainly a completely esterified product and an acyl chloride agent undergoing an acyl chloride reaction, and then undergoing a polymerization reaction with a diamine to obtain a viscous polyamide ester glue containing fat units, and the reaction formula is as follows:

[0069]

[0070] Method 2: The reaction product obtained in step S1) is imidazole-treated, and then the obtained material is polymerized with a diamine having a structure of formula c to obtain a viscous polyamide ester glue containing fat units. In this process, the reaction product obtained in step S1) is mainly a completely esterified product that is imidazole-treated to convert it into a diimidazole derivative, and then polymerized with a diamine to obtain a viscous polyamide ester glue containing fat units. The reaction formula is as follows:

[0071]

[0072] Method 3: The reaction product obtained in step S1) and the diamine having the structure of formula c are polymerized under the action of a condensing agent to obtain a viscous polyamide ester glue containing fat units; the condensing agent includes but is not limited to the following;

[0073]

[0074] The polymerization reaction of the present invention is carried out in a polar solvent, which includes but is not limited to N,N′-dimethylformamide (DMF), N,N′-dimethylacetamide (DMAc), N-methylpyrrolidone, dimethyl sulfoxide (DMSO), tetrahydrofuran / methanol mixture (THF / MeOH), etc.

[0075] In step S2) of the present invention, after the diamine having the structure of formula c and the reaction product obtained in step S1) are subjected to polymerization reaction, the product obtained in step S2) is subjected to imidization reaction to obtain a microporous polyimide film material containing fat units. The imidization reaction of the product obtained in step S2) is the same as the above, and will not be repeated.

[0076] The present invention provides a multi-microporous fat-unit-containing polyimide film material and a preparation method thereof. Aiming at the problem that the fat-unit-containing polyimide has good solubility but is difficult to phase separate during the imidization process, which is not conducive to pore formation, the present invention specifically grafts specific compounds containing ether bonds or ester groups and monohydroxyl-terminated poly (dimethylsiloxane) onto polymer molecular chains, and gradually phase separates uniformly inside the film as the chemical changes on the molecular chain occur, and gradually forms natural pores, which ensure uniform pore size while retaining the intrinsic properties of polyimide to the maximum extent. In addition, the present invention adopts the production process and production equipment of conventional polyimide films with the highest technical maturity and the highest production efficiency, which is more conducive to the large-scale production of porous polyimide films, and can also retain the intrinsic properties of polyimide materials to the maximum extent, eliminating the problems of film degradation and uneven pores and pore sizes caused by adding subsequent processing procedures. The microporous fat-unit-containing polyimide film material of the present invention is an insulating material with excellent dielectric properties, which is very suitable for use in high-speed, high-frequency integrated circuits. It can also be used to prepare a PI film with through pores on both sides to replace polyolefins as a lithium-ion battery separator as needed. BRIEF DESCRIPTION OF THE DRAWINGS

[0077] Figure 1 This is a SEM scanning morphology of micropores of the fat unit-containing polyimide film prepared in Example 1;

[0078] Figure 2 This is a SEM scanning morphology of micropores of the fat unit-containing polyimide film prepared in Example 2;

[0079] Figure 3 This is a SEM scanning morphology of micropores of the fat unit-containing polyimide film prepared in Example 3;

[0080] Figure 4 This is a SEM scanning morphology of micropores of the fat unit-containing polyimide film prepared in Example 4;

[0081] Figure 5 This is a SEM scanning morphology of micropores of the fat unit-containing polyimide film prepared in Example 5;

[0082] Figure 6 This is a SEM scanning morphology of micropores of the fat unit-containing polyimide film prepared in Example 6;

[0083] Figure 7 This is a SEM scanning morphology of micropores of the fat unit-containing polyimide film prepared in Comparative Example 1;

[0084] Figure 8 This is a SEM scanning morphology of the micropores of the fat unit-containing polyimide film prepared in Comparative Example 2. DETAILED DESCRIPTION

[0085] The present invention discloses a multi-microporous fat-unit-containing polyimide film material and a preparation method thereof. A person skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve the same. It should be particularly noted that all similar substitutions and modifications are obvious to a person skilled in the art and are considered to be included in the present invention. The method and application of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the method and application of this article without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention.

[0086] The test instruments, test conditions and methods for the performance test of the samples in the present invention are as follows:

[0087] 1. Micromorphology characterization: XL30 (FEI Company, USA) field emission environmental scanning electron microscope (SEM) was used to observe the micromorphology of the microporous polyimide film after gold spraying.

[0088] 2. Heat resistance: TGA-2 thermogravimetric analyzer (TGA), PerkinElmer, USA, heating rate 10°C / min, nitrogen atmosphere.

[0089] 3. Glass transition temperature: static thermomechanical analyzer (TMA Q400), the test atmosphere is nitrogen, the heating rate is 5°C / min, and the temperature range is 40°C to 400°C.

[0090] 4. Mechanical properties: Mechanical properties testing machine (Instron-1121), tensile rate 5mm / min, sample strip size 50mm×10mm, test results are the average of 10 test sample strips;

[0091] 5. Porosity test: The present invention adopts density calculation method. Use a mold knife to cut the porous film into 20mm×20mm square samples, weigh the film mass and measure its thickness, and calculate the density of the sample. The density of polyimide is 1.4g / cm 3 The porosity can be calculated by the following formula.

[0092]

[0093] Where ρ 1 is the sample density calculated based on mass and volume, ρ 0 is the density of polyimide.

[0094] The molecular weight of the monohydroxy-terminated poly(dimethylsiloxane) used in the specific embodiment of the present invention is in the range of 600 to 6000.

[0095] The present invention will be further described below in conjunction with embodiments:

[0096] Example 1

[0097] A 500mL three-necked round-bottom flask equipped with a nitrogen inlet and a mechanical stirrer was placed in a low-temperature cold bath and the temperature was set to 0°C. 9.806g of cyclobutanetetracarboxylic dianhydride (CBDA) and 120mL of N,N-dimethylacetamide were added to the three-necked flask. 7.9g of pyridine was added and mechanical stirring was started for about 30 minutes. 20.672g of propylene glycol monolaurate and 12.087g of poly(dimethylsiloxane) monohydroxyl-terminated were added to the reaction solution. After the addition was completed, the reaction was continued for 8h, and the low-temperature cold bath was turned off. The reaction solution was continued to react at room temperature for 15h.

[0098] After the esterification reaction is completed, turn on the low-temperature cold bath, set the initial temperature to -15°C, and after the cold bath temperature reaches the set temperature, add 20.7g DCC to the reaction bottle and continue stirring for about 30min, then add 10.012g diaminodiphenyl ether (ODA) in batches, add 100mL N,N-dimethylacetamide, control the reaction liquid temperature at around -5°C, after all ODA is added, set the cold bath temperature to -5°C and continue the reaction for 8h, and filter to obtain a viscous glue solution.

[0099] The viscous adhesive liquid synthesized above is degassed statically and then coated on a glass plate, and then placed in an 80°C film drying oven for 1 hour to completely solidify the film. The film is peeled off from the glass plate, and the peeled film is fixed on a hollow stainless steel frame and placed in a high-temperature oven. The oven temperature is raised from 120°C to 180°C and kept for 0.5 hour; the temperature is further raised to 250°C and kept for 0.5 hour to obtain a porous polyimide film containing fat units.

[0100] The microporous morphology of the prepared polyimide film is shown in Figure 1 As shown, Figure 1 This is a SEM scanning morphology of the micropores of the fat unit-containing polyimide film prepared in Example 1. The relevant performance characterization of the film is shown in Appendix 1.

[0101] Example 2

[0102] A 500mL three-necked round-bottom flask equipped with a nitrogen inlet and a mechanical stirrer was placed in a low-temperature cold bath with the temperature set to 0°C. 10.507g of cyclopentanetetracarboxylic dianhydride (CPDA) and 120mL of N,N-dimethylacetamide were added to the three-necked flask. 7.9g of pyridine was added and mechanical stirring was started for about 30 minutes. 11.856g of dipropylene glycol monomethyl ether and 12.087g of poly(dimethylsiloxane) monohydroxy-terminated were added to the reaction solution. After the addition was completed, the reaction was continued for 8h, and the low-temperature cold bath was turned off. The reaction solution was continued to react at room temperature for 15h.

[0103] After the esterification reaction is completed, turn on the low-temperature cold bath, set the initial temperature to -15°C, and after the cold bath temperature reaches the set temperature, add 20.7g DCC to the reaction bottle and continue stirring for about 30min, then add 10.012g diaminodiphenyl ether (ODA) in batches, add 100mL N,N-dimethylacetamide, control the reaction liquid temperature at around -5°C, after all ODA is added, set the cold bath temperature to -5°C and continue the reaction for 8h, and filter to obtain a viscous glue solution.

[0104] The viscous adhesive liquid synthesized above is degassed statically and then coated on a glass plate, and then placed in an 80°C film drying oven for 1 hour to completely solidify the film. The film is peeled off from the glass plate, and the peeled film is fixed on a hollow stainless steel frame and placed in a high-temperature oven. The oven temperature is raised from 120°C to 200°C and kept for 0.5 hour; the temperature is further raised to 300°C and kept for 0.5 hour to obtain a porous polyimide film containing fat units.

[0105] The microporous morphology of the prepared polyimide film is shown in Figure 2 As shown, Figure 2 This is a SEM scanning morphology of the micropores of the fat unit-containing polyimide film prepared in Example 2. The relevant performance characterization of the film is shown in Appendix 1.

[0106] Example 3

[0107] A 500mL three-necked round-bottom flask equipped with a nitrogen inlet and a mechanical stirrer was placed in a low-temperature cold bath and the temperature was set to 0°C. 14.711g of biphenyltetracarboxylic dianhydride (BPDA) and 120mL of N,N-dimethylacetamide were added to the three-necked flask. 7.9g of pyridine was added and mechanical stirring was started for about 30 minutes. 13.136g of triethylene glycol monomethyl ether and 13.570g of poly(dimethylsiloxane) monohydroxyl-terminated were added to the reaction solution. After the addition was completed, the reaction was continued for 8h, and the low-temperature cold bath was turned off. The reaction solution was continued to react at room temperature for 15h.

[0108] After the esterification reaction is completed, turn on the low-temperature cold bath, set the initial temperature to -15°C, and when the cold bath temperature reaches the set temperature, add 20.7g DCC to the reaction bottle and continue stirring for about 30min, then add 4.408g 1,4-butanediamine in batches, add 80mL N,N-dimethylacetamide, control the reaction liquid temperature at around -5°C, after all the 1,4-butanediamine is added, set the cold bath temperature to -5°C and continue the reaction for 8h, and filter to obtain a viscous glue solution.

[0109] The viscous adhesive liquid synthesized above is degassed statically and then coated on a glass plate, and then placed in an 80°C film drying oven for 1 hour to completely solidify the adhesive film. The adhesive film is peeled off from the glass plate, and the peeled adhesive film is fixed on a hollow stainless steel frame and placed in a high-temperature oven. The oven temperature is raised from 120°C to 180°C and kept for 0.5 hour; the temperature is further raised to 250°C and kept for 0.5 hour to obtain a porous fat-unit-containing polyimide porous film.

[0110] The microporous morphology of the prepared polyimide film is shown in Figure 3 As shown, Figure 3 This is a SEM scanning morphology of the micropores of the fat unit-containing polyimide film prepared in Example 3. The relevant performance characterization of the film is shown in Appendix 1.

[0111] Example 4

[0112] A 500mL three-necked round-bottom flask equipped with a nitrogen inlet and a mechanical stirrer is placed in a low-temperature cold bath and the temperature is set to 0°C. 10.906g of pyromellitic anhydride (PMDA) and 120mL of N,N-dimethylacetamide are added to the three-necked flask. 7.9g of pyridine is added and mechanical stirring is started for about 30 minutes. 13.136g of triethylene glycol monomethyl ether and 12.087g of poly(dimethylsiloxane) monohydroxy-terminated are added to the reaction solution. After the addition is completed, the reaction is continued for 8h, and the low-temperature cold bath is turned off. The reaction solution is continued to react at room temperature for 15h.

[0113] After the esterification reaction is completed, turn on the low-temperature cold bath, set the initial temperature to -15°C, and when the cold bath temperature reaches the set temperature, add 20.7g DCC to the reaction bottle and continue stirring for about 30min, then add 4.408g 1,4-butanediamine in batches, add 80mL N,N-dimethylacetamide, control the reaction liquid temperature at around -5°C, after all the 1,4-butanediamine is added, set the cold bath temperature to -5°C and continue the reaction for 8h, and filter to obtain a viscous glue solution.

[0114] The viscous adhesive liquid synthesized above is degassed statically and then coated on a glass plate, and then placed in an 80°C film drying oven for 1 hour to completely solidify the film. The film is peeled off from the glass plate, and the peeled film is fixed on a hollow stainless steel frame and placed in a high-temperature oven. The oven temperature is raised from 120°C to 200°C and kept for 0.5 hour; the temperature is further raised to 300°C and kept for 0.5 hour to obtain a porous polyimide film containing fat units.

[0115] The microporous morphology of the prepared polyimide film is shown in Figure 4 As shown, Figure 4 This is a SEM scanning morphology of the micropores of the fat unit-containing polyimide film prepared in Example 4. The relevant performance characterization of the film is shown in Appendix 1.

[0116] Example 5

[0117] A 500mL three-necked round-bottom flask equipped with a nitrogen inlet and a mechanical stirrer was placed in a low-temperature cold bath and the temperature was set to 0°C. 9.806g of cyclobutanetetracarboxylic dianhydride (CBDA) and 120mL of N,N-dimethylacetamide were added to the three-necked flask. 7.9g of pyridine was added and mechanical stirring was started for about 30 minutes. 9.612g of diethylene glycol monomethyl ether and 12.087g of poly(dimethylsiloxane) monohydroxy-terminated were added to the reaction solution. After the addition was completed, the reaction was continued for 8h, and the low-temperature cold bath was turned off. The reaction solution was continued to react at room temperature for 15h.

[0118] After the esterification reaction is completed, turn on the low-temperature cold bath, set the initial temperature to -15°C, and when the cold bath temperature reaches the set temperature, add 20.7g DCC to the reaction bottle and continue stirring for about 30min, then add 1,4-butanediamine in batches, add 80mL N,N-dimethylacetamide, control the reaction liquid temperature at around -5°C, set the cold bath temperature to -5°C after all ODA is added, and continue the reaction for 8h, then filter to obtain a viscous glue solution.

[0119] The viscous adhesive liquid synthesized above is degassed statically and then coated on a glass plate, and then placed in an 80°C film drying oven for 1 hour to completely solidify the film. The film is peeled off from the glass plate, and the peeled film is fixed on a hollow stainless steel frame and placed in a high-temperature oven. The oven temperature is raised from 120°C to 200°C and kept for 0.5 hour; the temperature is further raised to 300°C and kept for 0.5 hour to obtain a porous polyimide film containing fat units.

[0120] The microporous morphology of the prepared polyimide film is shown in Figure 5 As shown, Figure 5 This is a SEM scanning morphology of the micropores of the fat unit-containing polyimide film prepared in Example 5. The relevant performance characterization of the film is shown in Appendix 1.

[0121] Example 6

[0122] A 500mL three-necked round-bottom flask equipped with a nitrogen inlet and a mechanical stirrer was placed in a low-temperature cold bath and the temperature was set to 0°C. 9.806g of cyclobutanetetracarboxylic dianhydride (CBDA) and 120mL of N,N-dimethylacetamide were added to the three-necked flask. 7.9g of pyridine was added and mechanical stirring was started for about 30 minutes. 20.672g of propylene glycol monolaurate and 12.087g of poly(dimethylsiloxane) monohydroxyl-terminated were added to the reaction solution. After the addition was completed, the reaction was continued for 8h, and the low-temperature cold bath was turned off. The reaction solution was continued to react at room temperature for 15h.

[0123] After the esterification reaction is completed, turn on the low-temperature cold bath, set the initial temperature to -15°C, and when the cold bath temperature reaches the set temperature, add 20.7g DCC to the reaction bottle and continue stirring for about 30min, then add 14.617g 1,4-bis(4-aminophenoxy)benzene (1,4,4-APB) in batches, add 100mL N,N-dimethylacetamide, control the reaction liquid temperature at around -5°C, set the cold bath temperature to -5°C after all ODA is added, and continue the reaction for 8h, and filter to obtain a viscous glue solution.

[0124] The viscous adhesive liquid synthesized above is degassed statically and then coated on a glass plate, and then placed in an 80°C film drying oven for 1 hour to completely solidify the film. The film is peeled off from the glass plate, and the peeled film is fixed on a hollow stainless steel frame and placed in a high-temperature oven. The oven temperature is raised from 120°C to 200°C and kept for 0.5 hour; the temperature is further raised to 300°C and kept for 0.5 hour to obtain a porous polyimide film containing fat units.

[0125] The microporous morphology of the prepared polyimide film is shown in Figure 6 As shown, Figure 6 This is a SEM scanning morphology of the micropores of the fat unit-containing polyimide film prepared in Example 6. The relevant performance characterization of the film is shown in Appendix 1.

[0126] Comparative Example 1

[0127] Place a 500mL three-necked round-bottom flask equipped with a nitrogen inlet and a mechanical stirrer in a low-temperature cold bath and set the temperature to 0°C. Add 9.806g of cyclobutanetetracarboxylic dianhydride (CBDA) and 120mL of N,N-dimethylacetamide into the three-necked flask. Add 7.9g of pyridine and start mechanical stirring for about 30 minutes. Dissolve 16.420g of triethylene glycol monomethyl ether in 50mL of ether and add dropwise to the reaction solution. After the addition is completed, continue the reaction for 8h, turn off the low-temperature cold bath, and continue the reaction at room temperature for 15h.

[0128] After the esterification reaction is completed, the low-temperature cold bath is turned on, and the initial temperature is set to -15°C. After the cold bath temperature reaches the set temperature, 20.7g DCC is added to the reaction bottle and stirring is continued for about 30min. Then, 9.913g 4,4-diaminodiphenylmethane (MDA) is added in batches, and 100mL N,N-dimethylacetamide is added. The temperature of the reaction liquid is controlled at around -5°C. After all the MDA is added, the cold bath temperature is set to -5°C and the reaction is continued for 8h. The viscous glue solution is obtained by filtration.

[0129] The viscous adhesive liquid synthesized above is degassed statically and then coated on a glass plate, and then placed in an 80°C film drying oven for 1 hour to completely solidify the film. The film is peeled off from the glass plate, and the peeled film is fixed on a hollow stainless steel frame and placed in a high-temperature oven. The oven temperature is raised from 120°C to 200°C and kept for 0.5 hour; the temperature is further raised to 300°C and kept for 0.5 hour to obtain a porous polyimide film containing fat units.

[0130] The microporous morphology of the prepared polyimide film is shown in Figure 7 As shown, Figure 7 This is a SEM scanning morphology of the micropores of the fat unit-containing polyimide film prepared in Comparative Example 1. The relevant performance characterization of the film is shown in Appendix 1.

[0131] Comparative Example 2

[0132] A 500mL three-necked round-bottom flask equipped with a nitrogen inlet and a mechanical stirrer was placed in a low-temperature cold bath and the temperature was set to 0°C. 10.507g of cyclopentanetetracarboxylic dianhydride (CPDA) and 120mL of N,N-dimethylacetamide were added to the three-necked flask. 7.9g of pyridine was added and mechanical stirring was started for about 30 minutes. 12.662g of propylene glycol monolaurate and 30.821g of poly(dimethylsiloxane) monohydroxyl-terminated were added to the reaction solution. After the addition was completed, the reaction was continued for 8h. The low-temperature cold bath was turned off and the reaction solution was continued to react at room temperature for 15h.

[0133] After the esterification reaction is completed, the low-temperature cold bath is turned on, and the initial temperature is set to -15°C. After the cold bath temperature reaches the set temperature, 20.7g DCC is added to the reaction bottle and stirring is continued for about 30min. Then, 9.913g 4,4-diaminodiphenylmethane (MDA) is added in batches, and 100mL N,N-dimethylacetamide is added. The temperature of the reaction liquid is controlled at around -5°C. After all the MDA is added, the cold bath temperature is set to -5°C and the reaction is continued for 8h. 10g of poly(dimethylsiloxane) monohydroxy-terminated product is added to the glue solution, and it is fully stirred for 3h to obtain a viscous glue solution.

[0134] The viscous adhesive liquid synthesized above is degassed statically and then coated on a glass plate, and then placed in an 80°C film drying oven for 1 hour to completely solidify the film. The film is peeled off from the glass plate, and the peeled film is fixed on a hollow stainless steel frame and placed in a high-temperature oven. The oven temperature is raised from 120°C to 200°C and kept for 0.5 hour; the temperature is further raised to 300°C and kept for 0.5 hour to obtain a porous polyimide film containing fat units.

[0135] The microporous morphology of the prepared polyimide film is shown in Figure 8 As shown, Figure 8 This is a SEM scanning morphology of the micropores of the fat unit-containing polyimide film prepared in Comparative Example 2. The relevant performance characterization of the film is shown in Appendix 1.

[0136] Table 1

[0137]

[0138] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A microporous polyimide film material containing fat units, characterized in that: Obtained by imidization reaction of a material comprising a polyamide ester containing a fat unit having a structure of formula I; Wherein, said z≥1000; The Ar1 and Ar2 are independently selected from substituted or unsubstituted aromatic groups, substituted or unsubstituted heteroaromatic groups, and substituted or unsubstituted aliphatic groups, and the Ar1 and Ar2 are not simultaneously selected from substituted or unsubstituted aromatic groups or substituted or unsubstituted heteroaromatic groups; The M1 and M2 are independently selected from substituted or unsubstituted C1 to C 60 Aliphatic groups containing ether bonds, substituted or unsubstituted C1~C 60 Thioether-containing aliphatic groups, substituted or unsubstituted C1~C 60 An ester-containing aliphatic group or a poly(dimethylsiloxane) group, and the M1 and M2 are the same or different.

2. The microporous polyimide film material containing fat units according to claim 1, characterized in that: The M1 and M2 are independently selected from substituted or unsubstituted C3 to C 30 Ether-bonded aliphatic groups, substituted or unsubstituted C3~C 30 Thioether-containing aliphatic groups, substituted or unsubstituted C3~C 30 One of an ester-containing aliphatic group or a poly(dimethylsiloxane) group having a structure of Formula Ia; x≥1; The R is a fatty chain.

3. The microporous polyimide film material containing fat units according to claim 1, characterized in that: The polyamide ester containing fat units having the structure of formula I has a poly(dimethylsiloxane) group, and the molar amount of the poly(dimethylsiloxane) group accounts for 2% to 50% of the total molar amount of M1 and M2.

4. The microporous polyimide film material containing fat units according to claim 1, characterized in that: Ar1 has one or more structures of formula Ar1-a to formula Ar1-k; Ar2 has one or more structures of formula Ar2-a to formula Ar2-e; wherein X is selected from hydrogen, alkyl, cycloalkyl, aryl, fluoroalkyl, hydroxyl, alkoxy, phenoxy, cyano, nitro, amino, acetylamino, ester, acyl, halide or carboxyl; The y is independently an integer of 1 to 4; The R 1 and R 2 One independently selected from the groups represented by the structures of Formula 1 to Formula 13; Among them, the X 1 and X 2 independently selected from hydrogen, alkyl, cycloalkyl, aryl, fluoroalkyl, hydroxy, alkoxy, phenoxy, cyano, nitro, amino, acetamido, ester, acyl, halide or carboxyl; The R 3 It is selected from an alkyl group having C1 or more or a fluorinated alkyl group having C1 or more.

5. The microporous polyimide film material containing fat units according to claim 1, characterized in that: The microporous polyimide film material containing fat units has a structure of formula II; 6. The method for preparing the microporous polyimide film material containing fat units according to any one of claims 1 to 5, characterized in that: The following steps are involved: The material including the polyamide ester containing fat units is subjected to imidization reaction to obtain a microporous polyimide film material containing fat units.

7. The method for preparing the microporous polyimide film material containing fat units according to claim 6, characterized in that: The specific steps include: S1) reacting a monohydroxy compound with a dianhydride having a structure of formula a; the monohydroxy compound is selected from substituted or unsubstituted C3 to C 30 Ether-bonded aliphatic alcohols, substituted or unsubstituted C3~C 30 Thioether-containing aliphatic alcohols, substituted or unsubstituted C3~C 30 One or more of the ester-containing fatty alcohols and a monohydroxy-terminated poly(dimethylsiloxane) having a structure of formula b; S2) polymerizing the diamine having the structure of formula c and the reaction product obtained in step S1); H2N—Ar2—NH2 formula c; S3) performing an imidization reaction on the product obtained in step S2) to obtain a microporous polyimide film material containing fat units.

8. The method for preparing the microporous polyimide film material containing fat units according to claim 7, characterized in that: In step S1), the monohydroxy-terminated poly(dimethylsiloxane) accounts for 2% to 50% of the total amount of the monohydroxy compound.

9. The method for preparing the microporous polyimide film material containing fat units according to claim 7, characterized in that: In step S1), the reaction temperature is -5°C to 60°C, and the reaction time is 16h to 25h.

10. The method for preparing a microporous polyimide film material containing fat units according to any one of claims 6 to 9, characterized in that: The temperature of the imidization reaction is 50° C. to 350° C., and the time of the imidization reaction is 0.3 h to 30 h.

Citation Information

Patent Citations

  • Polyimide film having pores and method for producing same

    CN106414575A

  • Arnish for porous polyimide film production and method for producing porous polyimide film using same

    CN106661265A

  • High-performance transparent polyimide, polyimide film and preparation method thereof

    CN112961349A

  • Polyimide, preparation method thereof, composition and polyimide film

    CN117089068A

  • Method for manufacturing porous polyimide film and film

    JP2001151929A